Preventive Esophagomyobronchoplasty as a Reliable Prophylaxis of Bronchial Stump Failure and Bronchopleural Fistula after Pneumonectomy in Lung Cancer - R. A. Sulimanov; E. S. Spassky; R. R. Sulimanov; E. Y. Shestakova (Креативная хирургия и онкология)
Introduction. At present, bronchial stump failure after pneumonectomy ranges from 1% to 20%, and mortality — from 20 to 75%. In past decades, various methods of preventive bronchoplasty have been introduced and improved in order to reduce the incidence of the bronchial stump failure and bronchopleural fistula. However, the existing methods fail to prove their predominant effectiveness to be suggested as a “gold standard” for prevention of the bronchial stump failure during pneumonectomy. A method introduced by the authors enables an additional tissue mobilization with uncontrolled circulatory disturbance of the “biological flap” to be avoided. Aim. To evaluate the results and effectiveness of preventive esophagomyobronchoplasty in clinical practice. Materials and methods. The suture of “preventive esophagomyobronchoplasty” of the bronchial stump after pneumonectomy in lung cancer was developed and introduced into the clinical practice of the Thoracic Surgery Unit. The study involves a statistical analysis of bronchial stump failures as well as bronchopleural fistulas before and after the introduction of preventive esophagomyobronchoplasty. Results and discussion. A retrospective analysis of 224 clinical observations proves a zero probability of such complications after pneumonectomy as bronchial stump failure and bronchial fistula in case of preventive esophagomyobronchoplasty. The incidence of pleural empyema does not exceed 1.3%. Notably, pleural empyema implies longer duration of stay, additional examination, expensive drugs, as well as direct threatening life of a patient. Conclusion. Since 2015, when the new method of bronchial stump formation has been introduced into clinical practice, the rate of complications in the form of bronchial stump failure was reduced from 10.5% to 0%.